Determination of adulterations in dairy products and vegetable oils based on their fatty acid compositions - D. S. Bolshakov; D. V. Yudina; T. B. Nikeshina (Ветеринария сегодня)
Improved method for determination of fatty acid compositions of dairy and plant products that allows detection of adulterations in vegetable oils, milk and dairy products is described in the paper.